Children's Experiences of Welfare in Modern Britain - Pooley, Siân; Taylor, Jonathan (IHR Conference Series, 2021)
The history of childhood and welfare in Britain through the eyes of children. Children's Experiences of Welfare in Modern Britain brings together the latest historical research on welfare provision by the state, charities and families from 1830 to 1980. Demonstrating how the young were integral to the making, interpretation, delivery and impact of welfare services, the chapters consider a wide range of investments in young people's lives, including residential institutions, emigration schemes, hospitals and clinics, schools, social housing and familial care. Drawing upon thousands of personal testimonies, including a wealth of writing by children themselves, the book shows that we can only understand the history and impact of welfare if we listen to children's experiences.